2023
DOI: 10.1111/jvim.16654
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of magnetic resonance images for characterization of blood‐brain barrier dysfunction in dogs with brain tumors

Abstract: Background Blood‐brain barrier (BBB) permeability can be assessed quantitatively using advanced imaging analysis. Hypothesis/Objectives Quantification and characterization of blood‐brain barrier dysfunction (BBBD) patterns in dogs with brain tumors can provide useful information about tumor biology and assist in distinguishing between gliomas and meningiomas. Animals Seventy‐eight hospitalized dogs with brain tumors and 12 control dogs withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The BBBD score was the percentage of positive voxels representing permeability and was determined in a (LR) low range (mean of PID in temporal muscle plus 1 SD) and a (HR) high range (mean PID in temporal muscle plus 2 SD). Better differentiation of tumor class (88% extra-axial and 90% intra-axial) was achieved using HR, and a significant correlation between tumor size and BBBD score was observed [88]. HT BBBD score alone did not differ significantly between the two tumor classes.…”
Section: Perfusion Weighted Imagingmentioning
confidence: 91%
See 4 more Smart Citations
“…The BBBD score was the percentage of positive voxels representing permeability and was determined in a (LR) low range (mean of PID in temporal muscle plus 1 SD) and a (HR) high range (mean PID in temporal muscle plus 2 SD). Better differentiation of tumor class (88% extra-axial and 90% intra-axial) was achieved using HR, and a significant correlation between tumor size and BBBD score was observed [88]. HT BBBD score alone did not differ significantly between the two tumor classes.…”
Section: Perfusion Weighted Imagingmentioning
confidence: 91%
“…The advantage of SEA is that it is less technically and computationally demanding than DCE-MRI and can be readily performed on most open-source and proprietary image analysis software platforms. A two-armed study prospectively evaluated DCE-MRI and SEA and retrospectively the SEA of canine brain tumors [88]. Although the retrospective arm of the study included some histologically confirmed tumors, this was not a strict inclusion criterion, and no dogs in the prospective study arm had pathologically confirmed tumors, so this study was ultimately excluded from data extraction.…”
Section: Perfusion Weighted Imagingmentioning
confidence: 99%
See 3 more Smart Citations